PERTUMBUHAN DAN EFISIENSI PAKAN IKAN NILA (Oreochromis niloticus) YANG DIPUASAKAN SECARA PERIODIK - Yeni Sri Mulyani; Yulisman .; Mirna Fitrani (Universitas Sriwijaya, 2014)
ABSTRACT The aims of this research were to know the effect of periodical starvation on growth, survival rate, and feed efficiency of tilapia. The experimental fish weight was 8.945±0.185 g. Research used completely randomized design with five treatments and three replications. The treatments were fish subjected one day starvation and one day refeeding (P1), fish subjected one day starvation and two days refeeding (P2), fish subjected one day starvation and three days refeeding (P3), fish subjected one day starvation and four days refeeding (P4), fish subjected one day starvation and five days refeeding (P5) and fish fed daily (control). Fish were fed three times a day at 08.00 am, 12.00 pm, 05.00 pm using at satiation method. The results showed no significant differences in growth, survival rate and feed efficiency were observed at each treatments and control. This research showed that the best periodical starvation for growth, feed efficiency and survival rate of tilapia was P3. As long as the research, water quality was in optimum range for tilapia were temperature 27-29oC, dissolved oxygen 3.73-4.99 mg.L-1, pH 6.8-7.3, and ammonia 0.003-0.012 mg.L-1. Keywords: Starvation, growth, feed efficiency, tilapia